Ultrasonic assisted extraction (UAE) of moringa oleifera seed oil / Muhammad Zulfahmi Amat Rithuana ... [et al.] - Amat Rithuana, Muhammad Zulfahmi; Aiman Sumi, Muhammad Syafiq; Mhd Jamal, Nur Hanis; Shah Buddin, Meor Muhammad Hafiz; Mohd Fuad, Faiznur
This study aims to investigate Moringa oleifera seed oil extraction using indirect ultrasonication or known as ultrasonic assisted extraction (UAE). The process was conducted at power of l 76kW and ultrasonic frequency of 40 kHz. Usage of highly toxic and carcinogen solvent was avoided in this study by using ethyl acetate as replacement. The influence of extraction temperature, liquid to solid (LIS) ratio and time were looked at. Experimental data reveals that the maximum Moringa oleifera seed oil extraction (38.1%) was obtained at conditions; 30°C, LIS 1:20 after 40 mins of extraction. The study was followed by fitting the experimental data using three kinetics empirical models; Power law model, Parabolic diffusion model and Naik model to identify the best fit data. It was found that, Power law model fitted well to the extraction data with R2 value of0.9919. Thus, it is adequate to describe the extraction process of oil from Moringa oleifera seeds.